FAKTOR-FAKTOR YANG MEMENGARUHI VOLUNTARY AUDITOR SWITCHING (Media Riset Akuntansi, 2022)
The purpose of this study was to examine and analyze the effect of audit fees, managerial ownership, the percentage change in ROA, and financial distress on voluntary auditor switching. The population in this study are financial sector companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2020 period. The sampling technique used in this study was purposive sampling method and obtained a sample size of 114 during the study period. The analytical method used is logistic regression analysis using SPSS version 25 software. The results show that audit fees, managerial ownership, and the percentage change in ROA have no effect on voluntary auditor switching. Meanwhile, financial distress has a positive effect on voluntary audio switching.